The Business Case for Gender Diversity: Examining the Role of Human Resource Management Investments - Roh, Hyuntak; Kim, Eugene (Human Resource Management, 2016)
Integrating opposing theoretical perspectives from the past literature, the authors hypothesize and test a U‐shaped curvilinear relationship between gender diversity and workforce productivity. They further propose that the curvilinear effects vary depending on the levels of an organization's human resource management (HRM) investments in pay, benefit, training, and communication; that is, the patterns are more salient whenHRMinvestments are high rather than low. To enhance understanding of howHRMinvestments have impact on diverse employees, the authors also examine the moderating influence of organizational identification of diverse members that can exert proximal influence on the diversity‐productivity relationship. As predicted, results reveal that high levels ofHRMinvestments influence the gender diversity–workforce productivity association to form a U‐shaped curvilinear relationship. Organizational identification also yields the same moderating patterns. Research and practical implications are discussed. © 2015 Wiley Periodicals, Inc.